(untitled) - J Schwarzenbach (London, 1996)
The book provides a practical highly readable guide to the basic fundamentals and concepts of control. It is arranged in four chapters on closed loops and their models, dynamic behaviour of system components, analysis of feedback systems and design of feedback systems
Keywords: engineering mathematics